The university, problematic reality - Marías, Julian (2016)
The University of San Marcos de Lima asks me for a few words about “The University in the 20th century”. The occasion, its fourth centenary. The reason, the awareness that all the clear heads that move around the University have, that this is nothing simple and obvious today, that it can march without more and do the same as until now. The University of San Marcos de Lima is the oldest of the two Americas: Fifty-nine years after the discovery, a University was already rising along the edges of the Pacific. I am little friend of the emphasis, and I do not usually take pride in past Spanish or Latin American glories; I fear, rather, all those great gestures that people of our lineage usually make; but I also don't think that the shock that in our historical sensibility produces that date should be overlooked: 1551. And that long tradition of four centuries of authority to the University of Lima to ask today what happens to the University. Will I have any authority to try to give an answer? This is more than problematic.